ANALISIS GELOMBANG TERHADAP STRUKTUR BANGUNAN BREAKWATER TEGAK PANTAI TAPAK PADERI BENGKULU - Besperi Besperi; Agustin Gunawan; Mawardi Mawardi (Universitas Bengkulu, 2019)
This research is aimed to find out characteristic of waves and significant wave happened in breakwater building as the reference in analyzing the dimension of standing breakwater type. The researcher used wind data analysis and visual measurement of wave. Based on the analysis, the researcher found that the waves were fully developed seas condition. This condition was caused by fetch value which was long enough, so the height of wave reached maximum value. The lengths of fetch was 200 km and the significant height of wave (Hs) was 2,85 meters and the significant wave period (Ts) was 8,48 seconds. The stress force (p) was 46,274 tons and the moment (Mp) was 185,094 tonmeters. The lift force (U) was 11,674 ton and the moment (Mu) was 31,131 tonmeter.